Redesain Identitas Visual SMK Taruna Bangsa Kota Bekasi - Muhammad Furqon Nurfikri; Fauzan Aulia (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
SMK Taruna Bangsa, a Vocational High School, is poised to enhance its value and brand image in the field of education. However, the school faces shortcomings in implementing its visual identity across various activities. These include inconsistency in identity, an inapplicable identity system, suboptimal design principles, and a lack of interactivity aligned with the target audience. Consequently, the author undertakes a redesign of SMK Taruna Bangsa's visual identity, leveraging the existing concept developed over its more than 20 years of existence. The redesign follows the Research and Development 4D model, encompassing Define, Design, Develop, and Disseminate stages. Data analysis for this redesign employs the SWOT methodology (Strengths, Weaknesses, Opportunities, and Threats).